Projecting fed cattle price discovery over the next decade - Mintert, J.; Ward, C.E.; Peel, D.S.; Schroeder, Ted C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Interviews were conducted with cattle feeders, beef packers, and others involved in the beef industry to project how fed cattle prices will be discovered in the next decade. Respondents generally indicated that economics will determine beef’s market share in 2010, how important public grades and grading will be, and whether consumer brands for fresh beef will become common. Economics also will determine how much influence alliances will have, whether most cattle will be marketed by some value-based pricing system, and what changes will occur in market information and futures markets.
Keywords: Beef; Fed cattle price; Price discovery projections